A Conceptual Model to Assess the Literacy of Water Consumers - Fernandes, Ana (2022)
A conceptual model to assess the literacy level of water consumers is presented. On the one hand, a literature search was performed using the ScienceDirect and B-On platforms, conjoining the terms literacy, awareness, water, water for human consumption, drinking water, environmental, disease prevention and public health, resulting in seven papers with the mingle of literacy and water and five on literacy and the environment being uncovered. On the other hand, the lack of papers and information on the subject caused us to consider developing a conceptual model to transform the processes of planning and operationalization of the studies of literacy of water consumers. The model can support the development and validation of measurement tools capable of apprehending different dimensions in the context of water literacy. A questionnaire was conceived and applied to a cohort of 147 respondents in order to assess water literacy. In addition, the articulation of the proposed model and Deming’s PDCA model was demonstrated in order to achieve excellence through the evaluation of the current reality to promote improvement solutions.